The structure of liquid carbon elucidated by in situ X-ray diffraction - D. Kraus; J. Rips; M. Schörner; M. G. Stevenson; J. Vorberger; D. Ranjan; J. Lütgert; B. Heuser; J. H. Eggert; H.-P. Liermann; I. I. Oleynik; S. Pandolfi; et al. (Nature, 2025)
Abstract Carbon has a central role in biology and organic chemistry, and its solid allotropes provide the basis of much of our modern technology1. However, the liquid form of carbon remains nearly uncharted2, and the structure of liquid carbon and most of its physical properties are essentially unknown3. But liquid carbon is relevant for modelling planetary interiors4,5 and the atmospheres of white dwarfs6, as an intermediate state for the synthesis of advanced carbon materials7,8, inertial confinement fusion implosions9, hypervelocity impact events on carbon materials10 and our general understanding of structured fluids at extreme conditions11. Here we present a precise structure measurement of liquid carbon at pressures of around 1 million atmospheres obtained by in situ X-ray diffraction at an X-ray free-electron laser. Our results show a complex fluid with transient bonding and approximately four nearest neighbours on average, in agreement with quantum molecular dynamics simulations. The obtained data substantiate the understanding of the liquid state of one of the most abundant elements in the universe and can test models of the melting line. The demonstrated experimental abilities open the path to performing similar studies of the structure of liquids composed of light elements at extreme conditions.